Design, Synthesis, and Anticancer Activities of Novel 2-Amino-4-phenylthiazole Scaffold Containing Amide Moieties - Zhi-Hua Zhang; Hong-Mei Wu; Sai-Nan Deng; Xiao-Yu Cai; Yu Yao; Muriira Cyrus Mwenda; Jin-Yin Wang; Dong Cai; Yu Chen (Journal of Chemistry)
Appropriately substituted 2-amino-4-phenylthiazole derivatives were designed and synthesized according to the structural characteristics of crizotinib. The obtained compounds were characterized using 1H NMR, 13C NMR, and HRMS. The target compounds 5a–o were evaluated for their in vitro antiproliferative activity against A549, HeLa, HT29, and Karpas299 human cancer cell lines. Based on results of biological studies, some of these compounds exhibited significant antiproliferative activity. Compound 5b possessed outstanding growth inhibitory effects on the four cell lines, especially for HT29 cell with IC50 value of 2.01 µM. Along with the biological assay data, a molecular docking study suggests that the target compounds were a potential inhibitor.